2022
DOI: 10.1017/s0007114522003087
|View full text |Cite
|
Sign up to set email alerts
|

Mycoprotein ingestion within or without its wholefood matrix results in equivalent stimulation of myofibrillar protein synthesis rates in resting and exercised muscle of young men

Abstract: Ingestion of mycoprotein stimulates skeletal muscle protein synthesis (MPS) rates to a greater extent than concentrated milk protein when matched for leucine content, potentially attributable to the whole-food nature of mycoprotein. We hypothesised that bolus ingestion of mycoprotein as part of its whole food matrix would stimulate MPS rates to a greater extent compared with a leucine matched bolus of protein concentrated from mycoprotein. Twenty-four healthy young (age; 21±2 y, BMI; 24±3 kg.m2) males received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…protein content > 80 % of total mass). This likely explains the observed rapid increase in postprandial circulating insulin and amino acid concentrations, a finding consistent with recent studies (26,27) , and suggests pea protein to be an ideal source for stimulating tissue anabolism. In contrast, the aminoacidaemic response to lupin ingestion may have been delayed, or impaired, due to the high fibre content within its whole-food matrix (Table 3), which has been proposed to modulate the rise in postprandial amino acid concentrations (29,30) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…protein content > 80 % of total mass). This likely explains the observed rapid increase in postprandial circulating insulin and amino acid concentrations, a finding consistent with recent studies (26,27) , and suggests pea protein to be an ideal source for stimulating tissue anabolism. In contrast, the aminoacidaemic response to lupin ingestion may have been delayed, or impaired, due to the high fibre content within its whole-food matrix (Table 3), which has been proposed to modulate the rise in postprandial amino acid concentrations (29,30) .…”
Section: Discussionsupporting
confidence: 90%
“…Our data demonstrate low postprandial methionine availabilities following ingestion of both pea and lupin, an observation also observed previously (25,63) . This is of relevance since single in vivo amino acid deficiencies are proposed to provide substrate limitation to the continuation of postprandial MPS rates (64) , though we did not observe this in a recent study (27) .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, once other variables are introduced, such as comparing different protein sources (Chan et al, 2019; Churchward‐Venne, Breen, et al, 2014; Dideriksen et al, 2011; Reidy et al, 2013), isolated vs whole foods (Burd et al, 2015; Mitchell, McGregor, et al, 2015; Van Vliet et al, 2017), meal ingestion (Kim et al, 2016; Symons et al, 2011) or co‐ingestion with other macronutrients (Gorissen et al, 2014; Hamer et al, 2013; Koopman et al, 2007; Staples et al, 2011), the relationship is far less clear. We (Monteyne, Coelho, Porter, Abdelrahman, Jameson, Finnigan, et al, 2020; Monteyne, Coelho, Porter, Abdelrahman, Jameson, Jackman, et al, 2020; West et al, 2022) and others (Burd et al, 2015; Chan et al, 2019; Van Vliet et al, 2017) have observed a dissociation between circulating leucine concentrations and MPS in a series of recent studies, specifically involving whole food approaches. For example, a 25% greater MPS response was observed with ingestion of skim milk vs. beef despite a significantly lower plasma leucine concentration (Burd et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Recent research has studied whether bolus ingestion of mycoprotein (as part of its wholefood matrix) would stimulate MPS rates more than a leucine-matched bolus of protein concentrated from mycoprotein. It has been shown that protein consumption significantly raised plasma essential amino acid and leucine concentrations ( P < 0⋅0001), but more rapidly and to greater magnitudes when derived from the milk protein concentrate ( 26 ) . MPS synthesis, however, increased in rested and exercised muscle in both conditions indicating that the ‘form’ of delivery was irrespective.…”
Section: Mycoprotein Bioavailability and Resistance-training Muscle A...mentioning
confidence: 99%